Philosophy and the Biology of Male Homosexuality. Issue 7 (July 2015) - Lemeire, Olivier; De Block, Andreas
Abstract This paper is a review of how biological as well as other scientific theories, concepts and findings have been used to answer philosophical questions regarding the nature of male homosexuality. We argue that while these sciences are certainly relevant for present philosophical debates, few of the different philosophical issues surrounding male homosexuality can be settled by science alone. In the first section, we introduce a number of various essentialist and constructivist views on (male) homosexuality. The second section focuses on the innateness debate over homosexuality. In the last section, we assess the typically constructivist critiques of biological research into homosexuality.